Factors predicting change in hospital safety climate and capability in a multi-site patient safety collaborative: a longitudinal survey study. Issue 7 (5th May 2012) - Benn, Jonathan; Burnett, Susan; Parand, Anam; Pinto, Anna; Vincent, Charles
Abstract : Objective: The study had two specific objectives: (1) To analyse change in a survey measure of organisational patient safety climate and capability (SCC) resulting from participation in the UK Safer Patients Initiative and (2) To investigate the role of a range of programme and contextual factors in predicting change in SCC scores. Design: Single group longitudinal design with repeated measurement at 12-month follow-up. Setting: Multiple service areas within NHS hospital sites across England, Wales, Scotland and Northern Ireland. Participants: Stratified sample of 284 respondents representing programme teams at 19 hospital sites. Intervention: A complex intervention comprising a multi-component quality improvement collaborative focused upon patient safety and designed to impact upon hospital leadership, communication, organisation and safety climate. Measures: A survey including a 31-item SCC scale was administered at two time-points. Results: Modest but significant positive movement in SCC score was observed between the study time-points. Individual programme responsibility, availability of early adopters, multi-professional collaboration and extent of process measurement were significant predictors of change in SCC. Hospital type and size, along with a range of programme preconditions, were not found to be significant. Conclusion: A range of social, cultural and organisational factors may be sensitive to this type of intervention but the measurable effect is small. Supporting critical local programme implementation factors may be an effective strategy in achieving development in organisational patient SCC, regardless of contextual factors and organisational preconditions.